The Hand of the Interpreter. Edited by G.F. Mitrano and Eric Jarosinski - Stewart, Francis (Literature and theology, 2012)
The notion of being touched by a book is not an unusual one; we all have favourite stories and texts that we turn to time and again for a cathartic release or an emotional journey. This is in addition to the illumination and lessons those books inevitably provide. In The Hand of the Interpreter, G.F. Mitrano and Eric Jarosinki have gathered a collection of 14 essays that engage theoretically or practically with this concept of being touched by a book. The emotional and intellectual impact of a book is further linked with the physical experience of touching, holding, and progressing through the book as one reads it, feeling the weight transfer from one hand to another.